Economic and technological forecasting competencies of German energy companies: Empirical insights from annual reports - Kehrel, Uwe; Sick, Nathalie (International journal of energy sector management, 2014)
Purpose - This paper aims to extend the small body of literature on energy industry transitions on firm level. A growing number of articles shed light on paradigm shifts in the energy industry and the influence of renewable energies on industry structures. In the majority of cases, the authors analyze changes on a global or national level. Design/methodology/approach - Energy companies' forecasting capabilities are particularly important to enable them to react in time to upcoming changes in industry structures. In this context, we analyze annual reports of German energy companies to evaluate their economic and technological forecasting competencies. Findings - Big energy providers offer high economic forecasting quality, but seem to be less able to derive valid forecasts in terms of renewable energies from the currently unstable political frameworks. On the contrary, renewable energy companies do not seem to suffer from these difficulties and provide good foresting accuracy in terms of renewable energy development, but show less accurate economic forecasting quality. Practical implications - Big energy providers need to find the means of responding to the challenges and integrate changing political guidelines and support into their forecasting system. Renewable energy companies, in contrast, should focus on company-level profitability and the respective economic forecasting competencies. Originality/value - This paper makes a significant contribution to the literature on the subject of energy industry transitions by providing insights from publicly available data on firm level. The findings are highly relevant for managers of the energy industry and policy makers in this field.